2016
DOI: 10.1016/j.aquatox.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ecotoxicological protocol for the deep-sea fauna using the hydrothermal vent shrimp Rimicaris exoculata

Abstract: In light of deep-sea mining industry development, particularly interested in massive-sulphide deposits enriched in metals with high commercial value, efforts are increasing to better understand potential environmental impacts to local fauna. The aim of this study was to assess the natural background levels of biomarkers in the hydrothermal vent shrimp Rimicaris exoculata and their responses to copper exposure at in situ pressure (30MPa) as well as the effects of depressurization and pressurization of the high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 61 publications
(59 reference statements)
4
26
1
Order By: Relevance
“…LC 50 values for Cd ranged between 521 and 548 µmol/L for shrimp (Brown et al, 2017a). Experiments are usually carried out with spiked Cu and Cd concentrations in the µmol/L range (Auguste et al, 2016;Martins et al, 2017;Mevenkamp et al, 2017). Trace metals are an important part of the biogeochemical cycle of the surface sediment and should be well understood before mining commences.…”
Section: Introductionmentioning
confidence: 99%
“…LC 50 values for Cd ranged between 521 and 548 µmol/L for shrimp (Brown et al, 2017a). Experiments are usually carried out with spiked Cu and Cd concentrations in the µmol/L range (Auguste et al, 2016;Martins et al, 2017;Mevenkamp et al, 2017). Trace metals are an important part of the biogeochemical cycle of the surface sediment and should be well understood before mining commences.…”
Section: Introductionmentioning
confidence: 99%
“…This differential response may be related to the prominent role of the gill in harboring chemosynthetic symbionts and located at the interface between the internal milieu and external vent environment. Similarly, whilst the induction of metallothionein was significant in Rimicaris exoculata gill tissue after 72 h, this was not the case in muscle tissue (Auguste et al, 2016). In this latter case the differential response seen in different tissues of the shrimp was considered to result from differences in the route of uptake of the metal over the time course of the experiment.…”
Section: Sub-lethal Impacts Of Chronic Exposure Should Be Consideredmentioning
confidence: 98%
“…For example, copper concentrations from the mussel Bathymodiolus azoricus habitat on the Mid-Atlantic Ridge (MAR) have been recorded between 0.17 µM at ∼850 m water depth at Menez Gwen to 2 µM at ∼2,300 m water depth at Rainbow (Kádár et al, 2005) hydrothermal vent sites. Auguste et al (2016) established the effects of copper exposure on the expression of tissue metallothioneins and lipid peroxidation as well as effects of the activity of key antioxidant enzymes in different tissues of the hydrothermal vent shrimp Rimicaris exoculata collected from the TAG hydrothermal vent field on the MAR and maintained at 30 MPa and 10 • C. Shrimp were held in solutions of either ∼25 or ∼250 µg l −1 copper for 72 h, which were at least two orders of magnitude less than the 72-h LC 50 concentration of ∼35,000 µg l −1 for Palaemon varians at 0.1 MPa and 10 • C reported by Brown et al (2017a). Auguste et al (2016) demonstrated that even shrimp that have evolved to live in the metal-rich environment of a hydrothermal vent field (R. exoculata) are sensitive to copper exposure in solution.…”
Section: Sub-lethal Impacts Of Chronic Exposure Should Be Consideredmentioning
confidence: 99%
See 2 more Smart Citations